Answer:C. It has only one solution
Explanation:
The system of equations is expressed as
y = x + 2
Subtracting 2 from the left hand side and the right hand side of the equation, it becomes
x = y - 2 - - - - - - - - - 1
-x + 3y = 6
Multiplying the left hand side and the right hand side of the equation by - 1, it becomes
x - 3y = - 6
Adding 3y to the left hand side and the right hand side of the equation, it becomes
x = 3y - 6 - - - - - - - - 2
Equating equation 1 and equation 2, it becomes
y - 2 = 3y - 6
3y - y = - 2 + 6
2y = 4
y = 4/2 = 2
Substituting y = 2 into equation 1, it becomes
x = 2 - 2 = 0
The solutions are (0, 2)